2022
DOI: 10.3389/fgene.2022.961554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cellular senescence-related signature for the prediction of prognosis and immunotherapy response in colon cancer

Abstract: The study was conducted to construct a cellular senescence-related risk score signature to predict prognosis and immunotherapy response in colon cancer. Colon cancer data were acquired from the Gene Expression Omnibus and The Cancer Genome Atlas databases. And cellular senescence-related genes were obtained from the CellAge database. The colon cancer data were classified into different clusters based on cellular senescence-related gene expression. Next, prognostic differential genes among clusters were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…By integrating these and other datasets developers performed a systems biology analysis of cell senescence. At present, there are few studies on CSRGs in ECa, but a number of studies have shown that CSRGs signature can play a prognostic role in hepatocellular carcinoma, gastric cancer, bladder cancer, renal cell carcinoma, and colon cancer (17)(18)(19)(20)(21). However, the expression characteristics and prognostic significance of CSRGs in ECa remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating these and other datasets developers performed a systems biology analysis of cell senescence. At present, there are few studies on CSRGs in ECa, but a number of studies have shown that CSRGs signature can play a prognostic role in hepatocellular carcinoma, gastric cancer, bladder cancer, renal cell carcinoma, and colon cancer (17)(18)(19)(20)(21). However, the expression characteristics and prognostic significance of CSRGs in ECa remain unclear.…”
Section: Introductionmentioning
confidence: 99%